The Synaptic Dysregulation in Adolescent Rats Exposed to Maternal Immune Activation - Cieślik, Magdalena; Gassowska-Dobrowolska, Magdalena; Zawadzka, Aleksandra; Frontczak-Baniewicz, Małgorzata; Gewartowska, Magdalena; Dominiak, Agnieszka; Czapski, Grzegorz A.; Adamczyk, Agata (Frontiers in Molecular Neuroscience, 2021)
Maternal immune activation (MIA) is a risk factor for neurodevelopmental disorders in offspring, but the pathomechanism is largely unknown. The aim of our study was to analyse the molecular mechanisms contributing to synaptic alterations in hippocampi of adolescent rats exposed prenatally to MIA. MIA was evoked in pregnant female rats by i.p. administration of lipopolysaccharide at gestation day 9.5. Hippocampi of offspring (52- to 53-days-old rats) were analysed using transmission electron microscopy (TEM), qPCR and Western blotting. Moreover, mitochondrial membrane potential, activity of respiratory complexes and changes in glutathione system were measured. It was found that MIA induced changes in hippocampi morphology, especially in the ultrastructure of synapses, including synaptic mitochondria, which were accompanied by impairment of mitochondrial electron transport chain and decreased mitochondrial membrane potential. These phenomena were in agreement with increased generation of reactive oxygen species, which was evidenced by a decreased reduced/oxidized glutathione ratio and an increased level of dichlorofluorescein (DCF) oxidation. Activation of cyclin-dependent kinase 5, and phosphorylation of glycogen synthase kinase 3β on Ser9 occurred, leading to its inhibition and, accordingly, to hypophosphorylation of microtubule associated protein tau (MAPT). Abnormal phosphorylation and dysfunction of MAPT, the manager of the neuronal cytoskeleton, harmonized with changes in synaptic proteins. In conclusion, this is the first study demonstrating widespread synaptic changes in hippocampi of adolescent offspring prenatally exposed to MIA.